DAMPAK EKONOMI DIGITAL TERHADAP PERKEMBANGAN PASAR MODAL DI INDONESIA - Wallep, Imanuel Markutoja; Minami, Gabriela Putri; Rade , Stefanus Don (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2025)
This study analyzes the impact of the digital economy on the development of the capital market in Indonesia, focusing on infrastructure transformation, changes in investor behavior, funding innovation, and challenges and opportunities that arise in the digital era. The results show that digitalization has increased the accessibility, efficiency, and liquidity of the capital market through the adoption of technologies such as cloud computing, blockchain, and online investment platforms. The number of capital market investors jumped significantly, dominated by millennials who use mobile applications, while infrastructure innovations by KSEI cut transaction times and increased market capitalization. However, this transformation is also accompanied by challenges such as low financial literacy, cyber vulnerability, and regulations that lag behind technological developments. On the other hand, the digital economy opens up strategic opportunities, including the growth of the Islamic capital market, AI-based product innovation, and increased financial literacy and inclusion through digital education and micro-investment integration. This research recommends holistic strategies in the form of regulatory reform, strengthening digital security, synergies between stakeholders, and developing an inclusive and sustainable ecosystem. By optimizing the role of the digital economy, Indonesia's capital market has the potential to become a major pillar of national and regional economic growth